2015
DOI: 10.1039/c4cp05855k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin undoped tetrahedral amorphous carbon films: thickness dependence of the electronic structure and implications for their electrochemical behaviour

Abstract: In this paper we show that the electronic properties of ultrathin tetrahedral amorphous carbon (ta-C) films are heavily dependent on their thickness. By using scanning tunnelling spectroscopy, Raman spectroscopy, and conductive atomic force microscopy, it was found that a decrease of ta-C thickness from 30 to 7 nm leads to (i) the narrowing of the band gap; (ii) appearance of shallower monoenergetic traps as well as the increase of their concentration; (iii) the increase of the equilibrium concentration of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…With respect to this, we have observed a very strong correlation between the thickness and the average current going through the ta-C layers [12]. In addition, this same thickness dependency is strongly reflected in the electrochemical behavior (especially separation between the peak potentials in FcMeOH redox system) as discussed in more detail in [24].…”
Section: Changes In the Ta-c Film During Processingmentioning
confidence: 76%
“…With respect to this, we have observed a very strong correlation between the thickness and the average current going through the ta-C layers [12]. In addition, this same thickness dependency is strongly reflected in the electrochemical behavior (especially separation between the peak potentials in FcMeOH redox system) as discussed in more detail in [24].…”
Section: Changes In the Ta-c Film During Processingmentioning
confidence: 76%
“…20 The I D /I G of 0.37 AE 0.08 measured for the 10 at% Fe sample, is over twice than the 0.15 AE 0.02 measured for the reference ta-C, but still comparable to I D /I G values reported for ta-C lms in literature. 20,31,49 The higher I D /I G with increased Fe content points to an increased amount of sp 2 -clustering or total sp 2 -fraction in the Fe/ta-C matrix. 37 Therefore, added iron appears to have an effect on the carbon-carbon bonding in ta-C.…”
Section: Resultsmentioning
confidence: 99%
“…Complementary to the resistive sp 3 -rich bulk of ta-C, the surface of the lm is characteristically sp 2 -rich due to "ion peening"-growth model, as proposed by Caro et al 40 in a recent computational study utilizing machine-learned interatomic potential trained from ab initio data. Several other computational 31,41,42 as well as XAS, XPS, and EELS studies 18,43 have investigated the nature of ta-C and its sp 2 -rich surface structures. For example, Caro et al 42 showed that the surface of ta-C lms consisted of clustered olenic chains, with a lower ratio of ringed carbon structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations